Gestión documental y conservación de información en la Secretaria de la Hacienda Alejandra Industrial y Agrícolas Cañas S.A. de la ciudad de San Juan - Carrillo Avellán, Jeira María (2020)
The company does not have a system to the management of your documents so this study was developed with the purpose to define the requirements to subsequently implement a system that allows document management. Put into practice the culture of document management, to streamline processes, issuance anda retrieval of documents. According to the analysis carried out this will allow to the employees that they benefit by obtaining knowledge about document management and the processes that Will allow them file, produce, manipulate and consult various types of documents depending on the type of content have the same. Besides defining whta is the scope of the system. Conclusions are established that tells us that was success defined the necessary requirements for system development and enabling business development.